1987
DOI: 10.1044/jshr.3004.434
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Bases of Acoustic LRT in Nonstutterers, Mild Stutterers, and Severe Stutterers

Abstract: The simple reaction time paradigm, incorporating a variable foreperiod, was used to investigate relative contributions of the respiratory and laryngeal systems to mild and severe stutterers' prolonged acoustic laryngeal reaction time (LRT) values. Prephonatory kinematic data were analyzed in terms of frequency of initiation, timing, and organization of events executed to attain the functional physiological targets of respiratory inflation during foreperiods and phonation onset after foreperiods. Acoustic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous research has shown that adults who stutter tend to be slower than fluent speakers at initiating various speech-like movements, nonsense syllables, words, short phrases, and simple sentences (e.g. Adams & Hayden, 1976; Reich, Till & Goldsmith, 1981; Watson & Alfonso, 1987; Logan, 2003).…”
Section: Existing Models Of the Mechanisms That Underlie Disfluent Spmentioning
confidence: 99%
“…Previous research has shown that adults who stutter tend to be slower than fluent speakers at initiating various speech-like movements, nonsense syllables, words, short phrases, and simple sentences (e.g. Adams & Hayden, 1976; Reich, Till & Goldsmith, 1981; Watson & Alfonso, 1987; Logan, 2003).…”
Section: Existing Models Of the Mechanisms That Underlie Disfluent Spmentioning
confidence: 99%
“…Numerous experimental investigations have provided evidence to support the above statements. For example, Watson and Alfonso (1987) described subperceptual forms of stuttering at the acoustic level as certain irregularities such as isolated pitch pulses before continuous phonation. Using these criteria, they eliminated 22% of supposedly 'perceptually fluent' tokens of phonation before a reaction time task for mild stutterers and 27% of supposedly 'perceptually fluent' tokens of phonation for severe stutterers.…”
Section: Covert Forms Of Stuttering -Levelmentioning
confidence: 99%